2018
DOI: 10.1002/oby.22191
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Visceral Adipose Tissue Oxygenation by Blood Oxygen Level‐Dependent MRI in Zucker Diabetic Fatty Rats

Abstract: This work demonstrated the feasibility of BOLD-MRI for detecting the VAT oxygenation status in ZDF rats, and the BOLD-MRI signals were associated with insulin resistance and systemic metaflammation in ZDF rats during the development of obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
(73 reference statements)
0
2
0
Order By: Relevance
“…Body composition was assessed by magnetic resonance imaging (MRI) scan on gestational day 18. Mice were anesthetized with vaporized isoflurane (1.5%) to reduce respiratory motion artifacts and then imaged on a 3.0‐T MRI system (Magnetom Verio; Siemens, Erlangen, Germany) with an eight‐channel wrist coil as previously described . The volumes of the abdominal visceral WAT (vWAT, containing the perigonadal WAT [pWAT]) and subcutaneous WAT (scWAT, containing the inguinal WAT [iWAT]) were calculated for transverse sections via a manual threshold setting in ImageJ 1.41 (National Institutes of Health, Bethesda, Maryland).…”
Section: Methodsmentioning
confidence: 99%
“…Body composition was assessed by magnetic resonance imaging (MRI) scan on gestational day 18. Mice were anesthetized with vaporized isoflurane (1.5%) to reduce respiratory motion artifacts and then imaged on a 3.0‐T MRI system (Magnetom Verio; Siemens, Erlangen, Germany) with an eight‐channel wrist coil as previously described . The volumes of the abdominal visceral WAT (vWAT, containing the perigonadal WAT [pWAT]) and subcutaneous WAT (scWAT, containing the inguinal WAT [iWAT]) were calculated for transverse sections via a manual threshold setting in ImageJ 1.41 (National Institutes of Health, Bethesda, Maryland).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, diabetic rodent studies have found that R2* can be used to evaluate visceral adipose tissue oxygenation status (21). Thus, it is worth investigating whether R2* and T2 mapping can be used to evaluate the effectiveness of exercise prescription effectiveness.…”
Section: Introductionmentioning
confidence: 99%